Catalytic Conversion of Bamboo Meal to High‐Yield Furfural With Solid Acid Catalyst FePO4⋅2H2O. Issue 34 (7th December 2017) - Ye, Jun; Zhou, Minghao; Wang, Kui; Chen, Shuigen; Xu, Junming; Jiang, Jianchun
Abstract: Furfural has been identified as an attractive platform chemical for production of valuable bio‐based chemicals and bio‐fuels. Therefore, to exploit a new catalyst which directly synthesized furfural from biomass was meaningful. In this work, FePO4 ⋅2H2 O was novelty applied in H2 O/THF solvent system to produce furfural from bamboo meal. The influence of catalyst type, solvent type, catalyst dosage, reaction temperature and times on furfural production was comparatively evaluated. The results indicated that the FePO4 catalyst displayed an excellent catalytic activity over mineral acids, metal chlorate and solid acids, achieving the highest furfural yield of 90.5% (from d‐xylose) and 83.1 mol % (from bamboo meal) at 170 °C (60 min) and 180 °C (60 min), respectively. Moreover, characterization indicated that FePO4 can recrystallize after the reaction, which provided a convenience for the catalyst recovery. Considering the excellent catalytic activity and recovering characteristic of FePO4 catalyst, systematical research of this new technique was required before the process could be considered as an industrial scale. Abstract : An inexpensive FePO4 catalyst was novelty applied for furfural production. The highest yield of furfural was 83.1 mol % (15.4 wt %) under reaction conditions of 180 °C, 60 min and catalyst dosage 0.5 g. FePO4 acted as both homogeneous and heterogeneous catalyst, provided a convenience for the catalyst recycling.